2016
DOI: 10.1287/mksc.2016.0982
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Designs and Estimation for Online Display Advertising Attribution in Marketplaces

Abstract: O nline Display Advertising's importance as a marketing channel is partially due to its ability to attribute conversions to campaigns. Current industry practice to measure ad effectiveness is to run randomized experiments using placebo ads, assuming external validity for future exposures. We identify two different effects, i.e., a strategic effect of the campaign presence in marketplaces, and a selection effect due to user targeting; these are confounded in current practices. We propose two novel randomized de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(25 citation statements)
references
References 19 publications
(22 reference statements)
1
24
0
Order By: Relevance
“…Indeed, they demonstrate that their approach is superior to existing methods. Barajas et al (2016) develop new methods that separate the target selection component and the campaign effect of online display ads for millions of users. Braun and Damien (2016) demonstrate how to scale rejection sampling for large hierarchical Bayes models.…”
mentioning
confidence: 99%
“…Indeed, they demonstrate that their approach is superior to existing methods. Barajas et al (2016) develop new methods that separate the target selection component and the campaign effect of online display ads for millions of users. Braun and Damien (2016) demonstrate how to scale rejection sampling for large hierarchical Bayes models.…”
mentioning
confidence: 99%
“…In this case, more credit is assigned to these channels when it comes to low-value customers. As we work with the assumption that during the first purchase the customer only purchases a few goods to try the seller [4], it is natural that more searches are performed by users in the initial research and evaluation of the suitability of the potential seller. In both cases, other channels are not significant drivers of conversions for acquiring low-value and high-value clients.…”
Section: Objectives and Methodsmentioning
confidence: 99%
“…Barajas et al [4], Anderl et al [1], Sterne [27] Abhishek et al (Site 1) and Bryl (Site 3) reported that the use of heuristic attribution models is not proper for attribution purposes. Barajas et al [4] claim that heuristic models assign a value to each displayed and converting channel. However, they ignore hypothetical reaction without a user being in touch with the advertisement.…”
Section: Introductionmentioning
confidence: 99%
“…based on expectations of future demand, e.g., a car dealer advertising a temporary price reduction before a holiday weekend. Ad treatment often correlates with ad response--and possibly other marketing actions, such as temporary price reductions--creating a confounding correlation between ad levels and outcomes (Barajas et al 2016 (Becker and Murphy 1993;Tuchman, Nair and Gardete 2018). As a result, it may be difficult for advertisers to distinguish incremental effects of ads from consumers' baseline propensities to attend to the brand's ads.…”
Section: Measurement Challengesmentioning
confidence: 99%